Viscous heating of hybridized hydromagnetic MWCNTs-Fe3O4/water nanomaterial in a moving disk with non-uniform thermal model - S.O. Salawu; T.A. Yusuf; E.O. Fatunmbi; A.M. Obalalu (Next Nanotechnology)
The potential usefulness of hybrid nanofluid in biotechnology, medicine, heat exchangers, thermal enhancement, and others is steadily increasing. Meanwhile, the efficiency of nanofluid depends on the based fluid, nanoparticle size and type, and other entrenched dynamical fluid properties. Thus, this research examines the viscous heating of hybridized hydromagnetic MWCNTs-Fe3O4/water (Multi-walled carbon nanotubes-Iron III oxide/water) of nanofluid in a moving disk with a non-uniform thermal model. For the theoretical analysis, 75% of H2O, 20% of Fe3O4 and 5% of MWCNTs are considered with shape factors n1=n2=3.0. The Fe3O4 and MWCNTs hybridized nanoparticles in water-solvent give a promising approach to augment heat conductivity and magneto-nanofluid properties for advanced thermal distribution systems. A spatial temperature variation of a non-uniform thermal model is assumed to simulate practical phenomena. A similarity transformation of the governing model is done and solved by coupling a numerical shooting technique with a Runge–Kutta scheme. The tabulated and graphically presented results reveal that the thermal propagation rate is improved by 21.34% as 0.25 volume of NWCNTs-Fe3O4 nanoparticle is distributed in 0.5 volume of H2O solvent. Hence, the outcomes of this research provide noteworthy insights into the maximization and designing of thermal transport systems contributing to the advancement of thermal management efficiency.